The Control of Business Concentrations in Peru: Fundamental Bases for its Regulation - Zúñiga Fernández, Tania (2018)
This contribution analyzes the fundamental aspects for the regulation of the procedure for the prior evaluation of business concentration operations in Peru, under the international standards developed by UNCTAD, the OECD, the ICN and the European Union. The control of concentrations constitutes an instrument of competition policy complementary to the control of anti-competitive conducts and proposes the SIEC test (significant impediment to effective competition) with a focus on the anti-competitive effects in the structure of the market that concentrations may produce. This study is explained in the current context of the legislative debate after almost three decades of prolonged dilemma on the relevance of its implementation, in accordance with the constitutional foundation that establishes the role of the State to facilitate and monitor free competition in a social market economy.